Uma investigação sobre os saberes elementares matemáticos presentes em concursos para professores primários em Sergipe (1874-1924) - Silva, Heloísa Helena (2016)
This paper presents the results of a survey which aimed to investigate the mathematical basic knowledge present in contest exams for primary school teachers in Sergipe in the period of 1874 to 1924. To achieve this purpose, those tests were used as main sources, as well as decrees, laws, regulations, president messages of the State of Sergipe. Valente (2013); Chartier (1995), Julia (2001) and Chervel (1990) served as support for an understanding of the history of mathematics education and to an interpretation of the sources. As a result of that investigation, the exams types were identified as essay and resolution tests. It was included in those exams: Basic knowledge of integer operations; Broken and fractions; Reduction of fractions to decimals; Conversion capacity measures in Canadas and vice versa; Broken adding; The greatest common divisor; The least common multiple; GCD by decomposition; Decimal numbers; Decimal fraction; Decimal conversion into ordinary and vice versa; Theory and property of proportions; Proportional division and simple interest; Divisibility of prime numbers; Multiplying common fractions with four major cases; Numbers and figures; Surface measurements; Volume and length; Conversion capacity measures and length measures; Time and its multiples and submultiples; Rule of three; Numeric expressions with fractions; Repeating decimal composed. After identifying those contents in the exams and not identifying how they should have been dealt in the contest rules, decrees or programs, we chose to establish a possible relationship between what was identified in those exams and how they were addressed in written manuals by Antonio Trajano. Throughout the research methods, we could establish that candidates or members of the congregation who used to create the exams had this author as reference. This statement is based not only by the way the questions were designed as well as the way the candidates used to answer the exams proposed questions. It is possible to identify elements which connect knowledge of mathematical elementary manuals to resolutions of those tests for example, divisibility and prime numbers among themselves. A fact worth mentioning is that all these knowledge were not taken as a reference when choosing teachers for Primary Education. Finally, we can say that the mathematical basic knowledge present in those exams were closer to elementary arithmetical knowledge treated in primary education.